The elementary home economics teacher in the Division of Isabela a descriptive profile - Castaneda, Gloria S. 1922- (s.n.], 1971)
The study aimed to establish a descriptive profile of the home economics teacher in the division of Isabela. The basic method used was the normative survey with the questionnaire as the major tool.